O4 Does 'mental' simulation have any effect on team performance in surgery? a systematic review. (3rd November 2019) - Snelgrove, Huon; Gabbott, Ben; Tennant, Duncan
Abstract : Introduction: Simulation-based training in medical education has become a common method to develop both technical and non-technical skills in teams. Mental Simulation (MS) is the cognitive act of simulating a task in our heads to pre-experience tasks imaginatively. It has been used widely to improve individual and collective performance in fields outside healthcare and offers potential for more efficient training in time pressured surgical and medical team contexts. The study aims to review the available literature to determine the impact of mental simulation on team performance and non-technical skills Methods: Medline, Embase, British Educational Index, CINAHL, Web of Science Psycinfo, Cohrane databased were searched in the period 1994–2018. The primary outcomes measure was improvements in team performance and non-technical skills. Study quality of RCT trials was assessed using Consolidated Standards of Reporting Trials (CONSORT) scores. The reported impacts of MR in all included studies were mapped onto Kirkpatrick's framework for the evaluation of educational interventions. Results: Eight studies with 322 participants were identified which met the inclusion criteria, of which 6 were randomized trials, one a prospective pragmatic trial and one qualitative study. Three studies found MR to be effective in improving team non-technical skills. Mental simulation was described in terms of mental practice, mental rehearsal and mental imagery. To practice rehearsals, supplementary learning aids were used including expert cue scripts, video and one-to-one coaching. MR benefited team non-technical skills when it was specifically designed to do so, but was not an automatic consequence of technical mental rehearsal alone Conclusion: The majority of studies demonstrate benefits of MR for technical performance but only three show positive impacts on teamwork. Overall the studies were of moderate quality and lacked sufficient discriminatory focus to examine impacts on team work dynamics They also lacked sufficient methodology to examine impacts beyond the immediate experimentations. Future research should look at longitudinal mixed method evaluation designs and focus on real clinical teams. References: Anton NE, Bean EA, Hammonds SC, et al. Application of Mental Skills Training in Surgery: A Review of Its Effectiveness and Proposed Next Steps. J Laparoendosc Adv Surg Tech A 2017;27(5):459–69. doi: 10.1089/lap.2016.0656 Karl E. Weick KMSaDO. Organizing for High Reliability: Processes of Collective Mindfulness. In: Boin A, ed. Crisis Management. London: Sage 2008:31–66. Patel SR, Gohel MS, Hamady M, et al. Reducing errors in combined open/endovascular arterial procedures: influence of a structured mental rehearsal before the endovascular phase. J Endovasc Ther 2012;19(3):383–9. doi: 10.1583/11-3785R.1 Arora S, Aggarwal R, Sevdalis N, et al. Development and validation of mental practice as a training strategy for laparoscopic surgery. Surg Endosc 2010;24(1):179–87. doi: 10.1007/s00464-009-0624-y